Gender differences in mood state response to training periodization - Rohaly, K. A.; Pierce, E. F.; Hammer, W. L.; Pace, J. (Medicine & Science in Sports & Exercise, 1994)
Collegiate swimmers (M = 12, F = 17) completed a Profile of Mood States (POMS) in the early-season, mid-season, overtraining, and taper stages of a competitive season. Average daily training volumes were 3868, 6145, 9745, and 4300 m for each respective stage. Significant mood disturbance and fatigue score increases and vigor decrease occurred during overtraining compared to the other three stages. Vigor increased significantly during taper. No sex differences were found in any of the factors for any stage of the study. These results are similar to those revealed for mood responses to defined periodized stages of training. Implication: The POMS could serve as a cross-validation index of differential response to obvious stages in periodized training. One should not expect any between-sex difference in the nature of mood disturbances.